A Dual-Process Model of Reactions to Perceived Stigma. - Pryor. John B.
The authors propose a theoretical model of individual psychological reactions to perceived stigma. This model suggests that 2 psychological systems may be involved in reactions to stigma across a variety of social contexts. One system is primarily reflexive , or associative, whereas the other is ruled based or reflective. This model assumes temporal pattern of reactions to the stigmatized, such that initial reactions are governed by the reflexive system, whereas subsequent reactions or adjustments " are governed by the rule-based system. Support for this model was found in 2 studies. Both studies examined participants' moments-by-moment approach-avoidance reactions to the stigmatized The 1st involved participants' reaction to person with HIV/AIDS, and the 2nd, participants' reactions to 15 different stigmatizing conditions. -- (from the author)